PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN BAGIAN KANTOR PADA PT PLN (PERSERO) UPDK PEKANBARU - Edlin, Ika Putri; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The problem in this study is the problem of employee discipline in work. Employee insciplined caused delays in a number of jobs and impacted the resulting performance was less than optimal.  In this case the leadership has an important role to influence employees in working to achieve the company's goals.  The purpose of this study was to find out the influence of transformational leadership and incentives on the performance of office employees at PT PLN (Persero) UPDK Pekanbaru. This research uses a type of explonatory research with quantitative approach. Data collection techniques carried out by using coesioner. The analytical techniques used are simple linear regeresi, multiple linear regression, determination coefficient test, t test and f test. Data analysis using linear regression analysis with the help of SPSS 20 software. The population used is the census method, namely all employees of the office section at PT PLN (Persero) UPDK Pekanbaru as many as 52 people. The results of this study show that transformational leadership affects employee performance. Providing incentives affects employee performance. And transfoermasional leadership and incentives affect the performance of office employees at PT PLN (Persero) UPDK Pekanbaru.    Keywords: transformational leadership influence and employee incentives and performance